PENGARUH MODEL PEMBELAJARAN MAKE A MATCH BERBASIS POP UP BOOK TERHADAP HASIL BELAJAR AKIDAH AKHLAK - Sofita Angraini; Deden Makbuloh; M Indra Saputra (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
The low learning outcomes of students in the subject of Akidah Akhlak at MA Al Hikmah Bandar Lampung is a problem that needs to be addressed immediately. The results of observations and interviews show that many students have difficulty understanding basic concepts and thinking analytically, especially in answering questions at the C4 cognitive level. In addition, the lack of student involvement in learning is another factor that worsens academic achievement. Therefore, a learning model that can stimulate active student participation and improve their analytical skills is needed. This study aims to examine the effect of the Make a Match learning model based on Pop-Up Books on the Akidah Akhlak learning outcomes of 10th grade students at MA Al Hikmah Bandar Lampung. This study uses a quantitative approach with a quasi-experimental design and a post-test only control group design. The sample was taken using simple random sampling, with class X B as the experimental group and X A as the control group. The experimental group participated in learning using the Make a Match model, which was carried out in several syntactic stages, such as matching question and answer cards, active discussion, and awarding points. The instrument used was a multiple-choice test that had been tested for validity and reliability, focusing on the C4 cognitive level. The results of data analysis using the t-test show that there is a significant effect of the Make a Match learning model based on Pop-Up Books on improving student learning outcomes, with a significance value of 0.001 (P < 0.05). In conclusion, this model is effective in creating active and enjoyable learning and is able to improve students' analytical skills in the subject of Aqidah Akhlak.